2010
DOI: 10.1243/14680874jer605
|View full text |Cite
|
Sign up to set email alerts
|

Spray stability of outwards opening pintle injectors for stratified direct injection spark ignition engine operation

Abstract: Citation: Marchi, A., Nouri, J. M., Yan, Y. & Arcoumanis, C. (2010). Spray stability of outwards opening pintle injectors for stratified direct injection spark ignition engine operation. International Journal of Engine Research, 11(6), pp. 413-437. doi: 10.1243/14680874JER605 This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract: The spray characteristics of three prototype piezo-electric pintle-type injectors was investigated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Two injections of fuel results in a lower effective injector orifice area compared to a single fuel injection with the effective area decreasing with an increasing number of injections. Marchi et al [43] found that a lower needle lift reduced the hollow cone fuel spray penetration length for both homogenous and stratified injection timings in an optical engine. A lower effective needle lift and injector orifice area is expected to result in a reduced fuel spray penetration length and a decrease in the piston crown fuel film mass based on these results.…”
Section: Imagingmentioning
confidence: 99%
“…Two injections of fuel results in a lower effective injector orifice area compared to a single fuel injection with the effective area decreasing with an increasing number of injections. Marchi et al [43] found that a lower needle lift reduced the hollow cone fuel spray penetration length for both homogenous and stratified injection timings in an optical engine. A lower effective needle lift and injector orifice area is expected to result in a reduced fuel spray penetration length and a decrease in the piston crown fuel film mass based on these results.…”
Section: Imagingmentioning
confidence: 99%
“…Their results demonstrated that a large degree of cyclic variation existed when the time delay after start of injection (SOI) was closer to its time of the opening response. Marchi et al (2010) assessed the spray stability of the injector by analyzing the mean and root mean square (rms) images of the fuel spray. Their results revealed that the positive-step inward seal band design injector produced the most repeatable spray among their three prototype SIDI injectors.…”
Section: Introductionmentioning
confidence: 99%
“…To get a quantitative information on the liquid deformation in the near-nozzle area root mean square images (RMS) were created from a sequence of snapshots (750 images), see Figure 4 b), in PCO Picture Viewer 1 . The analysis of visual data using RMS images was also performed in previous works such as (Marchi et al 2010, Zaremba et al 2017. The pixel intensities in the RMS image are computed by calculating the standard deviation of the pixel intensities of the image sequence.…”
Section: Image Post-processingmentioning
confidence: 99%